2019
DOI: 10.1111/os.12470
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Differences in Patients with Solitary and Multiple Spinal Metastases

Abstract: Objectives To investigate the association between the number of metastases to the spine and survival in patients with metastatic spinal cord compression (MSCC), as well as the prognosis difference between patients with solitary spinal metastasis (SSM) and multiple spinal metastases (MSM). Methods Three institutional databases were searched to identify all patients who had undergone spinal surgery for metastatic spinal tumors between March 2002 and June 2010. As well as age and gender, preoperative medical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(72 reference statements)
3
2
0
1
Order By: Relevance
“…In our study, KPS scores at BM diagnosis less than 80 were associated with a worse prognosis compared to scores ranging from 80 to 100. This is in line with previous researches that have identified performance status as one of the most valuable prognostic factors for survival of BM patients (16)(17)(18).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, KPS scores at BM diagnosis less than 80 were associated with a worse prognosis compared to scores ranging from 80 to 100. This is in line with previous researches that have identified performance status as one of the most valuable prognostic factors for survival of BM patients (16)(17)(18).…”
Section: Discussionsupporting
confidence: 92%
“…J Gastrointest Oncol 2021 | http://dx.doi.org/10.21037/jgo-20-586 The multiple bone involvement was found to be an independent prognostic factor for CSS, similar to some previous studies (15,16). However, Lun et al reported there was no association between the number of bone metastases and survival (17). Such differences might due to the sample size and selection bias in different studies.…”
Section: Discussionsupporting
confidence: 76%
“…The multiple bone involvement was found to be an independent prognostic factor for CSS, similar to some previous studies [15,16]. However, Lun et al reported there was no association between the number of bone metastases and survival [17]. Such differences might due to the sample size and selection bias in different studies.…”
Section: Treatments For Bmsupporting
confidence: 82%
“…Токухаси и соавт. рекомендовал эксцизионную операцию для пациентов с хорошим прогнозом (оценка Токухаси 12-15), паллиативную операцию для большинства пациентов со средним прогнозом (оценка 9-11) и консервативное лечение для пациентов с оценкой 8 или менее баллов [8,45,46,47]. Они проспективно применили свою систему подсчета баллов к 118 пациентам, чтобы помочь определить хирургическую стратегию, и обнаружили хорошую корреляцию между прогностическим показателем и фактической выживаемостью (r = 0,57, значительный P <0,0001), с коэффициентом согласованности между прогнозируемой и фактической выживаемостью 86,4.…”
Section: рис 3 классификация Weinsteinunclassified